A ocupação da terra na formação do municipio de Ourinhos-SP - Araujo, Débora Fernandes de; Cunha, Fabiana Lopes da [UNESP] (My University, 2011)
This Project searchs, through a dialogue between the History and Geography ciencies, to understand the history of the Ourinhos municipality formation process since the analysis of how the occupation in the Paranapanema´s Valley region came about (especially the west area in São Paulo´s state) through the Fronties of Expansion and Pioneering.We intend in our analysis to salvage the main elements of this historial conjecture that contributed to the municipality formation: with prominence to the performance of posseiros, pioneers and the farmers. This way we will work on the project the concernent aspects to the lands possession in São Paulos´s west on its different shades and refl ections, relationing its to the group of people who were important for the culture of coffee and the expansion of the railroad. This study, whose theme is part of a project more ambicious with public nature – Nos trilhos da memória e na memória dos trilhos ( At the memory tracks and at the tracks of the memory): The expansion and the new structure of the Historical Museum of Ourinhos – approved through the proclamation FAPESP/VITAE (Case nº 2006/57425-0), corresponds to a very important form of understanding the lands occupation and the formation of the municipality of Ourinhos.

A pesquisa busca, através de um diálogo entre a História e a Geografi a, compreender o processo histórico de formação do município de Ourinhos a partir da análise de como se deu a ocupação da região do Vale do Paranapanema (especifi - camente a região do Oeste Paulista) através das Frentes de Expansão e Pioneira. Pretendemos em nossa análise resgatar os principais elementos desta conjuntura histórica que contribuíram para a formação do município: com destaque para a atuação dos posseiros, pioneiros e fazendeiros. Desta maneira, trabalharemos aqui os aspectos concernentes à posse da terra no Oeste Paulista em seus diferentes matizes e refl exos, relacionando-os à cultura itinerante do café e a expansão da ferrovia. Este estudo, cujo tema faz parte de um projeto mais ambicioso e de cunho coletivo - Nos Trilhos da Memória e a Memória dos Trilhos: A Expansão e Revitalização do Museu Histórico de Ourinhos - aprovado através do edital FAPESP/VITAE (n°. Processo 2006/57425-0), é de suma importância para a compreensão da ocupação da terra e da formação do município em questão.
Keywords: History; Cofee; Ourinhos; História; Café; Ourinhos